FORESIGHT OF SAKHA REPUBLIC (YAKUTIA): CONCEPT AND BASIC MODELS OF THE PROJECT - V. S. Efimov; A. V. Lapteva; В. С. Ефимов; А. В. Лаптева (Novosibirsk State University of Economics and Management, 2015)
The necessity for the multidisciplinary research of reproduction (socio-cultural and demographic) of people in Sakha Republic (Yakutia) in the external (outer civilization) conditions is proved. Basic models and concepts for investigation of these processes are proposed. The necessity and the concept of Foresight of Sakha Republic (Yakutia), as a socio-constructive action, aimed at the formation of «vision of the future» in the long term the time horizon of two generations, are proved and introduced. The vision of the future includes: basic trends of changes in economics, demography, culture; possible critical situations, the field of possible scenarios and roadmap for movement into the future. The project results will form the basis of cultural and socio-economic policies that will ensure the reproduction of culture and languages of the Sakha Republic (Yakutia), their full integration into modern civilization processes. Обоснована необходимость мультидисциплинарного исследования воспроизводства (социально-культурного, демографического) народов Республики Саха (Якутия) в условиях внешних (иноцивилизационных) воздействий; предложены базовые модели и концепты для исследования данных процессов. Обоснована необходимость и представлена концепция Форсайта Республики Саха (Якутия) как социально-конструктивного действия, направленного на формирование «видения будущего» в долгосрочной перспективе – временной горизонт два поколения. Видение будущего включает: базовые тенденции происходящих изменений в области экономики, демографии, культуры; возможные критические ситуации, поле возможных сценариев и дорожную карту движения в будущее. Результаты проекта станут основой культурной и социально-экономической политики, обеспечивающей воспроизводство культуры и языков народов Республики Саха (Якутия), их полноценную интеграцию в современные цивилизационные процессы.